Makna Tari Inai Pada Masyarakat Melayu Desa Pekan Labuhan Kota Medan - DEBBI YOLANDA PUTRI (Universitas Negeri Medan, 2017)
This research is the study of the meaning of the Malay community henna Dance Village Medan Labuhan week. Henna dance illustrates the gratitude of the bride who will run the new household. This dance is accompanied by music which will be played ny through tool tools needed. In casting the results of this study using using some theories that support to research topics include the theory of meaning, form theory, the notion of dance as well as the understanding of henna. When the study is used to discuss about henna dance for three months, namely in June-August 2016. The study is in the village of Medan Labuhan week. The sample in this study were two traditional leaders. Data collection techniques including observation, interviews, literature study and documentation. Based upon the results of research conducted showed that the overall meaning contained in henna dance symbolizes the sense of family happiness bride to bride who will perform the wedding. Dance Henna is an understanding and awareness for the bride and groom that he will be given a sign that will determine and change on the day-to-day life to come. Thus, the sign is not to be taken lightly. The bride and groom will be escorted understanding and awareness to enter a new living space. The room is much different from that lived during this time. Through dance facing the henna, the bride was given a deep understanding of his life for a change. A change that must be gone through with caution, to maintain trust family as implied in the offerings menginai wedding dance.Keywords: Labuhan Malay society, dance Henna